FACTORS THAT INFLUENCE YOUTH PARTICIPATION IN DECISION MAKING IN COMMUNITY PROJECTS IN WAJIR EAST DISTRICT, WAJIR COUNTY - Ali, Abdullahi Ahmed; Kalung'e, Thuranira Moses (International Journal of Entrepreneurship and Project Management, 2018)
Purpose: Youth need a chance to develop their various communities through participation in decision making on projects that can bring about the beautification of their community without depending on the government. This study examined the factors that influence participation of youth in decision making in community projects in the Wajir East district, Wajir County. The study was guided by the objectives of finding out the influence of gender on participation of youth in decision making in community projects, investigating the influence of cultural factors on participation of youth in decision making in community projects, finding out the influence of educational level on participation of youth in decision making in community projects and investigating on the influence of government policies on participation of youth in decision making in community projects in Wajir East district, Wajir County. Methodology: This study adopted the descriptive survey research design. The target population of this study comprised of 24, 066 youth, aged between 18-35 years in Wajir East district, Wajir County. This study used simple random sampling to select 380 youths from the total youth in Wajir East district, Wajir County. The primary research instrument used in the study was a questionnaire and an interview guide was used also for specific leaders. The sample data from the survey was subjected to descriptive statistical data analysis methods -SPSS and presented in form of tables, figures and charts. The data was interpreted in form of descriptions, frequencies and percentages. Results: The findings and the conclusion of the study were that youth were mostly ignored in decision making in community projects in the area of study due to the influence of unfavorable government policies, low levels of education, cultural practices as well as gender imbalances. Unique Contribution to Theory, Practice and Policy: This study recommended that youth participation should be valued in Wajir County and Kenya at large to ensure that all citizens take part in development activities, government policies should be formulated which create room for every person to participate in spite of the differences in academic qualifications as well as gender, and that gender and culture should be overlooked in the current world so that every person can participate fully in decision making on community projects for more success